Web application design and implementation for Firefox OS - Theodorides, Michael (Τμήμα Ηλεκτρολόγων Μηχανικών και Μηχανικών Ηλεκτρονικών Υπολογιστών και Πληροφορικής, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2014)
This thesis aims at arguing that web applications on the desktop or the mobile are the future of software development. It uses as an example a webRTC based chatting application. The first introductory part touches the subject of web applications. We introduce the communication applications as there are today. We illustrate the strengths and weaknesses of web applications as well as the challenges and problems we faced. The second and third parts deal with the design and implementation respectively. They go into details of design principles, decisions and compromises that we made. As well as interesting implementation tricks. The fourth and fifth parts concentrate on evaluation and conclusion. We discuss what we have designed and implemented. We also evaluate how the final implementation meets our expectations. Finally, we wrap up with a few thoughts on future plans, and the subject of real time communication and web applications.
Keywords: Web Applications; Software Development; Communication Applications; Διαδικτυακή εφαρμογή